CHALLENGES AND OPPORTUNITIES FOR IMPROVING THE INVESTMENT CLIMATE IN UZBEKISTAN - Saidova , Subhinigor Azizovna (Educational Research in Universal Sciences, 2023)
The research work aims to develop scientific and practical recommendations for improving the investment climate in Uzbekistan. In recent years, owing to the immensity of the challenges and a lack of institutional and human capacity, the government will have to focus on tackling the impact of the COVID-19 pandemic and the related economic fallout (including the collapse of global energy prices, reduced Chinese demand and the return of labor migrants from abroad.)This presentation aims to give some insights into the investment environment and the analyses of factors influencing it. The findings of the study will benefit both local investors and foreign investors who are interested in assessing investment opportunities in Uzbekistan.